The Evaluation of Music Education Doctoral Program in Terms of Content and Application within the Scope of Uludag University Sample - Demirbatır, Rasim Erol (European Journal of Social Science Education and Research, 2014)
Music, with its various functions in human life, is not only an instrument of education but also a field of it. Basically, music education leads an individual to develop a behavior, or forms a behavioral change by changing and developing a gained behavior. Music education is carried out in a planned and programmed way at every level, from kindergarten to university. Besides the training of individuals through music, this situation necessitates some individuals, chosen especially for this training, to be trained in particular fields of music. In Faculties of Education within Turkey’s Higher Education System, the specialization in the field of Music Education in Master’s Degree level has been put into practice with the Higher Education Law No.2547, which took effect in 1982, and institutions were able to constitute only some parts of their academic staff with master’s programs opened until 1990s. There has been a more active education for the last 20 years; however, there isn’t satisfactory music education in our country especially in PhD level. Uluda? University Education Faculty the Department of Music Education (1982) is the fourth well-established educational institution in our country in terms of the date of establishment subsequently after Ankara (1924), ?stanbul (1969), ?zmir (1973). It has a more than 30-year-experience and knowledge. Master’s Degree Education has been carried out since 1986. Up to now, there have been many graduates, significant contribution to the art and culture of Music with many studies carried out different fields of Music Education, and many scholars have been trained. As of 2013, within Uluda? University Institute of Educational Sciences, Music Education PhD Program has been opened and the education is carried on since then. in this paper, there will be evaluations and introductions in terms of education, syllabus and application regarding this program.